Your undergraduate dissertation - Walliman, Nicholas S. R. (Los Angeles : SAGE, 2014)
This guide to all the essential facets of dissertation writing at undergraduate level provides advice for preparing a project and choosing a topic, and guidelines for writing a project proposal and producing a literature review.
Keywords: Dissertations, Academic; Academic writing; Academic writing; Dissertations, Academic